1990
DOI: 10.1176/ajp.147.6.685
|View full text |Cite
|
Sign up to set email alerts
|

The relation between alcohol problems and the anxiety disorders

Abstract: The idea that people suffering from anxiety have a proclivity to consume alcohol to relieve their symptoms is supported by reports showing high comorbidity rates of alcohol and anxiety problems. The authors reviewed relevant epidemiologic surveys, family studies, and field studies and conclude that the relationship between alcohol problems and anxiety appears to be variable among the anxiety disorders. In agoraphobia and social phobia, alcohol problems appear more likely to follow from attempts at self-medicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
71
1
1

Year Published

1991
1991
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 571 publications
(77 citation statements)
references
References 55 publications
4
71
1
1
Order By: Relevance
“…An association between increased anxiety states and ethanol abuse has been inferred in human studies [48] and animal studies [43, 49, 50], but several preclinical reports indicated an opposite relationship [51, 52, 53]. For example, it has been found that selectively bred low-anxiety behavior (LAB) rats drank more than high-anxiety behavior (HAB) counterparts [52].…”
Section: Discussionmentioning
confidence: 99%
“…An association between increased anxiety states and ethanol abuse has been inferred in human studies [48] and animal studies [43, 49, 50], but several preclinical reports indicated an opposite relationship [51, 52, 53]. For example, it has been found that selectively bred low-anxiety behavior (LAB) rats drank more than high-anxiety behavior (HAB) counterparts [52].…”
Section: Discussionmentioning
confidence: 99%
“…Anxiety disorders in childhood can seriously disrupt the course of children’s development, impairing school functioning and family and social relationships (Essau, Conradt, & Petermann, 2000; Ezpeleta, Keeler, Erkanli, Costello, & Angold, 2001; Strauss, Frame, & Forehand, 1987). Moreover, the presence of an anxiety disorder in childhood is associated with an increased risk for the development of additional anxiety disorders, depression, and substance abuse in adolescence and adulthood (Kim-Cohen et al, 2003; Kovacs, Gastsonis, Laulauskas, & Richards, 1989; Kushner, Sher, & Beitman, 1990). Left untreated, anxiety disorders persisting into adulthood are associated with considerably reduced health-related quality of life and serious occupational impairments (Comer et al, 2011; Merikangas et al, 2007).…”
mentioning
confidence: 99%
“…Findings obtained in this research suggest limitations of influential models of alcohol addiction, including the self-medication model (Khantzian, 1985;Quitkin et al, 1972), the substance-induced enhancement model (Kushner et al, 1990;Zvolensky et al, 2003), and the allostatic model (Koob & Le Moal, 2005;2008), each of which imply causal associations between emotional disorders and AUDs. All of the ORs for the reported contrasts fell within the small-to-moderate effect range for dichotomous predictors (Lipsey & Wilson, 2001) except for the OR resulting from the between-groups contrast for the I1 interval for anxiety disorders, which denoted a moderate-to-large effect.…”
Section: Discussionmentioning
confidence: 86%
“…Alternatively, emotional disorders may be concomitants or consequences of prob-lematic alcohol use (Fergusson et al, 2009;Merikangas et al, 1996;Swendsen et al, 1998) and, perhaps, have a role in AUD maintenance and relapse (Blume et al, 2000;Brown et al, 2008;Kushner et al, 2000). The allostatic (Koob & Le Moal, 2005, 2008 and substance-induced enhancement models of addiction (Kushner et al, 1990;Zvolensky et al, 2003), for example, suggest that multiple intoxication and withdrawal experiences increase susceptibility to anxious and depressed moods, and that these negative mood states, in turn, occasion subsequent substance use. Findings from retrospective (Falk et al, 2008;Merikangas et al, 1998) and prospective (Fergusson et al, 2009;Kushner et al, 1999;Zimmermann et al, 2003) studies as well as conclusions from literature reviews (e.g., Boden & Fergusson, 2011;Brown et al, 2008;Conner, 2011;Kushner et al, 2000;Raimo & Schuckit, 1998;Sher et al, 2005;Swendsen & Merikangas, 2000) further imply that emotional disorders may have complex relationships with AUDs that are, in part, influenced by maturational processes (e.g., changes in alcohol consumption patterns over the lifetime), cultural factors (e.g., cultural variations in patterns of alcohol consumption), and psychiatric history complexity (e.g., other co-occurring psychiatric disorders or the aggregation of disorders over the lifetime).…”
mentioning
confidence: 99%